The Effect of Using Catfish Feed, Pollard Flour, and Rice Bran as a Hatching Substrate of Black Soldier Fly Larvae - Anang Widigdyo; Rani Arifah Normawati (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2022)
BSF larvae have become a concern of researchers because it is a source of protein that can be used as an alternative feed. It also benefits the environment in the food cycle process and waste reduction. These various potentials must be balanced with an optimal BSF larvae cultivation process, using suitable materials to produce good and quality BSF larvae. Therefore, it is necessary to know the composition of good BSF larvae hatching media, considering that hatching is the initial stage of BSF larvae cultivation which determines the growth process of BSF larvae. This study aims to choose the best medium between a mixture of catfish feed with pollard flour and rice bran. By knowing the optimal media for the growth of BSF larvae, optimal BSF larvae results will be obtained so that the provision of BSF larvae can be achieved economically. The method used is experimental method by applying two treatments and six replications. The parameters measured were the average body weight of the BSF larvae and the body length of the 8-day-old BSF larvae. The results then was analyzed using an independent statistical t-test. The results showed that the second treatment of a mixture of 250 grams of catfish feed with 250 grams of pollard flour was the best medium for maggot cultivation, with the results of 7,607 Â± 1,505 body length and 0.153 Â± 0.582 body weight.